Blockchain technology and smart contracts in decentralized governance systems - Adam P. Balcerzak; Elvira Nica; Elżbieta Rogalska; Miloš Poliak; Tomáš Klieštik; Oana-Matilda Sabie (Administrative Sciences, 2022)
The aim of our systematic review was to inspect the recently published literature on decentralized governance systems and integrate the insights it articulates on blockchain technology and smart contracts by employing Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Throughout January and May 2022, a quantitative literature review of ProQuest, Scopus, and the Web of Science databases was carried out, with search terms including "city" + "blockchain technology", "smart contracts", and "decentralized governance systems". As the analyzed research studies were published between 2016 and 2022, only 371 sources satisfied the eligibility criteria. A Shiny app was harnessed for the PRISMA flow diagram to include evidence-based acquired and handled data. Analyzing the most recent and relevant sources and leveraging screening and quality assessment tools such as AMSTAR, Dedoose, Distiller SR, ROBIS, and SRDR, we integrated the core outcomes and robust correlations related to smart urban governance. As data visualization tools, for initial bibliometric mapping dimensions were harnessed, together with layout algorithms provided by VOSviewer. Future research should investigate smart contract governance of blockchain applications and infrastructure using decision-making tools and spatial cognition algorithms.
Keywords: 350; blockchain technology; decentralized governance system; smart city analytics; smart contract; urban sensing technology